Analysis of Number Material in Seventh-Grade Mathematics Teaching Materials Based on Praxeology - Putri, Astiwi Comastika; Sujadi, Imam; Laila Fitriana (Department of Mathematics Education Program IPI Garut, 2024)
Ketersediaan buku teks matematika yang tidak sesuai dapat mempengaruhi rendahnya kinerja akademik siswa. Penelitian ini bertujuan untuk menganalisis bahan ajar matematika sekolah dari perspektif praxeologis, di mana peneliti berusaha memahami bagaimana siswa berinteraksi dengan materi yang disajikan dalam bahan ajar, bagaimana mereka membuat keputusan tentang masalah mana yang akan diselesaikan, dan bagaimana desain serta konten buku teks mempengaruhi hasil belajar mereka. Ini adalah implementasi paradigma interpretatif dalam penelitian desain didaktik. (DDR). Melalui studi dokumen (dalam penelitian kualitatif yang dirancang secara fenomenologis) pada bahan ajar matematika sekolah Indonesia versi Kurikulum Merdeka, hasil yang diperoleh adalah: Komponen tugas (T) dalam materi tentang bilangan besar menggunakan teknik operasional; Komponen teknik (τ) sesuai karena informasi yang disampaikan dalam setiap pertemuan memiliki kontinuitas; Komponen teknologi (θ) belum sesuai, sehingga perbaikan dan peningkatan diperlukan dalam pengembangan media pembelajaran berbasis teknologi informasi dan komunikasi; dan Komponen teori (Θ) belum sepenuhnya selaras dengan teori konstruktivis, di mana siswa dapat membangun pengetahuan berdasarkan pengalaman masing-masing.The availability of mathematics textbooks that are not appropriate can influence students' low academic performance. This research aims to analyze school mathematics teaching materials from a praxeological perspective, where the researcher seeks to understand how students engage with the material presented in the teaching materials, how they make decisions about which problems to solve, and how the design and content of textbooks affect their learning outcomes. This implements the interpretive paradigm in didactical design research (DDR). This study will involve three principal stages in the data analysis procedure. Through document studies (in phenomenologically designed qualitative research) on the Indonesian school mathematics teaching materials version of the Merdeka Curriculum, the results obtained are: The task component (T) in the material on large numbers uses operational techniques; The technique component (τ) is appropriate because the information conveyed in each meeting has continuity; The technology component (θ) is not yet appropriate, so improvements and enhancements are needed in the development of information and communication technology-based learning media; and The theory component (Θ) is not yet fully aligned with constructivist theory, where students can build knowledge based on their respective experiences. The praxeological study of this teaching module provides a new perspective on how task design plays an important role in making the presentation of material more acceptable to students.